‘None-the-wiser’? Citizenship education in preventing radicalisation: contrasting European and Middle East perspectives - Gaffney, Francis; Silke, Andrew (Taylor & Francis, 2024)
Radicalisation towards violent extremism within educational settings has emerged as a high profile and critical issue in many contemporary societies. Debates around the appropriate role of educational institutions should play in this regard have attracted intense media and public debate both in the UK and internationally. This research involved face-to-face interviews with 51 education sector professionals in Europe and the Middle East to establish an evidence base regarding current practice regarding the understanding of radicalisation and building young people’s resilience to violent extremism through Citizenship Education (CE). The results highlighted a range of the limitations and shortfalls perceived by staff in CE provision and delivery including failings with how CE was delivered; the negative impact of limited time allocation on CE activity; and staff apprehension regarding their role and the role CE potentially plays in countering extremist behaviour. Some implications in terms of policy and practice in this area are identified.
Keywords: Radicalisation; citizenship education; countering extremist behaviour/activity; interviews; interpretative phenomenological analysis (IPA); snowball sampling; 5205 Social and Personality Psychology; 44 Human Society; 4402 Criminology; 52 Psychology; 4408 Political Science; 4 Quality Education; 4402 Criminology